2018
DOI: 10.1108/apjml-06-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning one-warehousen-retailer routing model in inter-store stock transfer operations of an international retail chain distribution

Abstract: Purpose The effectiveness of product replenishment and responsiveness of customer service delivery impact largely on satisfaction and retention of customers in retail chain logistics distribution. The fast moving goods in the complex delivery network and limited vehicle resource often lead to long customer waiting time in stock replenishment. With lack of literature systematically reviewing factors affecting retail distribution in inter-store stock transfer services and improving the operations, the purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For the proposed theoretical model, this study finds the influence of online to offline on chain stores. Both mediating and moderating roles indicate that chain store operators must cultivate both offline and online operations as an overall management strategy (He et al, 2020; Wang et al, 2018; L. Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For the proposed theoretical model, this study finds the influence of online to offline on chain stores. Both mediating and moderating roles indicate that chain store operators must cultivate both offline and online operations as an overall management strategy (He et al, 2020; Wang et al, 2018; L. Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Also, this collaborative approach may be useful to reduce the buffering efforts further (Aktas et al, 2020). The similar retail warehouse buffering concept has been presented by Wong et al (2018), wherein the inter-stock sharing model is adopted reducing transport efforts and losses to improve sales and customer satisfaction. Recenlty, Mar et al (2021) suggested that retailers can store and re-deliver the product from their location to improve distributions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GHG emissions are usually proportional to the amount of vehicle fuel consumption (Demir et al , 2012). Therefore, the main part of the delivery is to establish an efficient distribution system to reduce TC (Wong et al , 2018).…”
Section: Introductionmentioning
confidence: 99%